2016
DOI: 10.3847/0004-637x/818/1/84
|View full text |Cite
|
Sign up to set email alerts
|

TWO MASSIVE WHITE DWARFS FROM NGC 2323 AND THE INITIAL–FINAL MASS RELATION FOR PROGENITORS OF 4–6.5 M*

Abstract: We observed a sample of 10 white dwarf candidates in the rich open cluster NGC 2323 (M50) with the Keck LowResolution Imaging Spectrometer. The spectroscopy shows eight to be DA white dwarfs, with six of these having high signal-to-noise ratio appropriate for our analysis. Two of these white dwarfs are consistent with singly evolved cluster membership, and both are high mass ∼1.07 M e , and give equivalent progenitor masses of 4.69 M e . To supplement these new high-mass white dwarfs and analyze the initial-fi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 73 publications
5
47
1
Order By: Relevance
“…Data have been obtained studying WDs in, e.g., wide binaries ) and in clusters (Kalirai et al 2014;Cummings et al 2015, and references therein). Cummings et al (2016) found a tight relation between the main sequence mass M MS and the final mass M f , M f = 0.154 M MS + 0.261, up to ≈ 4 M , beyond which the relation appears less steep reaching M f ≈ 1.2 M at M MS = 8 M , Fig. 11.…”
Section: The Total Mass Lost By An Agb Starmentioning
confidence: 80%
See 2 more Smart Citations
“…Data have been obtained studying WDs in, e.g., wide binaries ) and in clusters (Kalirai et al 2014;Cummings et al 2015, and references therein). Cummings et al (2016) found a tight relation between the main sequence mass M MS and the final mass M f , M f = 0.154 M MS + 0.261, up to ≈ 4 M , beyond which the relation appears less steep reaching M f ≈ 1.2 M at M MS = 8 M , Fig. 11.…”
Section: The Total Mass Lost By An Agb Starmentioning
confidence: 80%
“…There is good evidence that AGB stars with masses up to 6-8 M manage to end their AGB evolution with a core mass below the Chandrasekhar limit of about 1.4 M (Cummings et al 2016). Most of the mass loss occurs on the AGB, except for the lower-mass stars where mass loss on the RGB is substantial in a relative sense, of the order 0.25 M in total (McDonald et al 2009(McDonald et al , 2011Lebzelter and Wood 2011).…”
Section: The Total Mass Lost By An Agb Starmentioning
confidence: 99%
See 1 more Smart Citation
“…With the advent of wide-field imagers and multi-object spectrographs on larger telescopes over the past 15 years, there has been an explosion of new white dwarf data. Namely in NGC 2099 (Kalirai et al 2005), Praesepe (Dobbie et al 2006a;Casewell et al 2009), NGC 6791 (Kalirai et al 2007), NGC 6819 and NGC 7789 (Kalirai et al 2008), NGC 2287 and NGC 3532 (Dobbie et al 2009), NGC 2618 (Williams et al 2004;, Kalirai et al (2014) and Cummings et al (2015;2016a;2016b), which analyzed newly discovered white dwarfs and uniformly analyzed previous data publicly available. Green points show the Pleiades white dwarfs connected only kinematically to the cluster (Dobbie et al 2006b).…”
Section: A Brief Historymentioning
confidence: 99%
“…To begin to address both of these limitations, Cummings et al (2015;2016a;2016b) have searched for new massive white dwarfs and have done detailed self-consistent analysis of both the white dwarf spectroscopy and open cluster photometry. For the wellstudied brightest white dwarfs, however, the parameters from the identical spectroscopic analysis in Gianninas et al (2011) Cummings (2009) and the automated fitting techniques of Bergeron et al (1992).…”
Section: Recent Progressmentioning
confidence: 99%